Killing cancer cells using nanotechnology: novel poly(I:C) loaded liposome–silica hybrid nanoparticles1. Issue 37 (7th October 2015) - Colapicchioni, Valentina; Palchetti, Sara; Pozzi, Daniela; Marini, Elettra Sara; Riccioli, Anna; Ziparo, Elio; Papi, Massimiliano; Amenitsch, Heinz; Caracciolo, Giulio
<x xml:space="preserve">Abstract</x> Synthesized core–shell liposome–silica hybrid nanoparticles (LSH NPs), when loaded with the anti-cancer polyinosinic–polycytidylic acid (poly(I:C)), exhibit high anti-tumoral activity in prostate and breast cancer cells.